FOLSPR aptamer sensor based on AuNPs polymer and its preparation method and application
By using the Aunps polyetroleum and the DON nucleic acid suitable ligand in the FolSpr sensor, the problem of insufficient signal response when detecting the DON when detecting the DON is used, and the DON detection of high sensitivity and specificity is achieved.
Patent Information
- Application Number
- CN202210745548.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-28
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-06-28
AI Technical Summary
When detecting DON, existing FOLSPR sensors have problems such as the fiber end surface AuNPs are prone to agglomeration or fall off, the LSPR signal strength is low, and the response to DON signal is weak, which affects the detection sensitivity and accuracy.
Adopt the FolSpr sensor based on Aunps polyette, and fix the Don nucleic acid adaptation of the sparsely modified DON nucleic acid on the AUNPS polyette through golden sulfur bonds to build a sensor platform for multi -modular nude fiber. The "hotspot" effect significantly enhances the signal.
Highly sensitive detection of DON is achieved, the sensitivity of the sensor is improved, the minimum detection limit is reduced to 0.05ng/mL, and the specificity and accuracy of the detection are improved.
Smart Images

Figure CN115165807B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of FOLSPR (fiber optional localized Surface Plasmon Resonance) detection technology, and in particular relates to a FOLSPR aptamer sensor based on AuNPs polymers and a preparation method and application thereof. Background Art
[0002] The scientific name of vomitoxin is deoxynivalenol (DON), which is the most important type B compound of the trichothecenes produced by Fusarium graminearum. DON is soluble in organic reagents and slightly soluble in water. It can bind to ribosomes, inhibit the synthesis of proteins, RNA and DNA, and induce cell apoptosis. Long-term intake of low concentrations of DON will damage the health of humans and animals. When excessive DON is ingested, it will cause poisoning reactions such as vomiting, diarrhea, anorexia, nausea, and nervous disorders, and may even damage the hematopoietic system and cause death. DON has high chemical stability, high temperature resistance, and weak acid resistance. It can exist stably and not be degraded during feed and food processing and storage, but alkaline environment can reduce the toxicity of DON. A large number of studies have confirmed that DON has similar heat resistance and pressure resistance to other fungal toxins. Studies have shown that DON is very stable and has a low concentration when baked at 170-350°C during food processing. DON is not as toxic as aflatoxin, but it must be considered an important food safety issue because DON is a common mycotoxin in foods such as wheat, corn, barley and their derivatives, and is commonly found in crops used for food and feed production throughout the world.
[0003] Currently, the determination of DON and its derivatives in food is carried out by isotope dilution liquid chromatography-tandem mass spectrometry, immunoaffinity chromatography cleanup high performance liquid chromatography, thin layer chromatography determination and enzyme-linked immunosorbent screening. However, traditional DON detection methods often require professional technicians, expensive reagents and instruments, complex sample preparation processes, long detection cycles and can only be completed in the laboratory. Fiber LSPR sensors have become a hot topic in the field of analytical detection due to their small size, low cost, high sensitivity and no labeling.
[0004] Most of the traditional FOLSPR sensors use noble metal nanoparticle monomers as sensing materials. Taking the FOLSPR sensor based on AuNPs monomer as an example, this type of sensor has the disadvantages of AuNPs on the end face of the optical fiber being prone to agglomeration or shedding, low LSPR signal intensity, and weak response to DON signals, which seriously interferes with the generation of LSPR offset signals. In recent years, plasma coupling caused by interference between noble metal nanoparticles is an effective method to improve sensitivity. AuNPs are arranged at a distance of several nanometers to form nanogaps, which can effectively enhance the interaction between light and nanostructures and significantly enhance the electromagnetic field intensity in the confined area through the "hot spot" effect. Stronger plasma electromagnetic enhancement can produce more absorption, which is very sensitive to changes in the refractive index around the nanoparticles. By constructing AuNPs polymers, a large number of nanogap structures can be generated, thereby achieving signal amplification and improving sensor sensitivity. Summary of the invention
[0005] Purpose of the invention: The technical problem to be solved by the present invention is to provide a FOLSPR sensor based on AuNPs polymers to achieve high-sensitivity detection of DON.
[0006] The technical problem to be solved by the present invention is to provide a preparation method and application of a FOLSPR sensor based on AuNPs polymers.
[0007] The final technical problem to be solved by the present invention is to provide a method for detecting DON toxin, which is based on the FOLSPR sensor and the "hot spot" effect of AuNPs polymers to sensitively detect DON in food.
[0008] Technical solution: In view of the above technical problems to be solved, the present invention provides a FOLSPR biosensor based on AuNPs polymers, wherein the FOLSPR biosensor is obtained by fixing a thiol-modified DON nucleic acid aptamer on the AuNPs polymer via a gold-sulfur bond.
[0009] Wherein, the sequence of the DON nucleic acid aptamer is 5'-(SH)-(CH2)6-GCA TCA CTA CAG TCA TTACGC ATC GTA GGG GGG ATC GTT AAG GAA GTG CCC GGA GGC GGT ATC GTG TGA AGT GCTGTC CC-3'.
[0010] Wherein, the particle size of the AuNPs polymer is 16-28nm.
[0011] The present invention also includes a method for preparing the FOLSPR biosensor based on AuNPs polymers, comprising the following steps:
[0012] 1) Assembling AuNPs polymer optical fiber:
[0013] 2) The thiol-modified DON nucleic acid aptamer is fixed on the optical fiber assembled with AuNPs polymer.
[0014] Wherein, the optical fiber of assembling AuNPs polymer in step 1) comprises the following steps:
[0015] 1.1) Preparation of AuNPs;
[0016] 1.2) Cleaning and hydroxylation of the optical fiber end face;
[0017] 1.3) The modified optical fiber of step 1.2) is immersed in the APTES solution;
[0018] 1.4) The modified optical fiber in step 1.3) is modified with AuNPs via gold-ammonia bonds;
[0019] 1.5) The optical fiber modified in step 1.4) is treated with PETMP to modify the AuNPs on the optical fiber with thiol groups;
[0020] 1.6) The optical fiber treated in step 1.5) is further assembled through Au-S bonds to obtain an optical fiber of AuNPs polymers.
[0021] Among them, the concentration of APTES solution in step 1.3) is 1.0%, the APTES treatment time is 2 to 18 hours, the AuNPs treatment time for the optical fiber in step 1.4) is 1 to 8 hours, the PETMP treatment time in step 1.5) is 1 to 5 hours, and the treatment time in step 1.6) is 1 to 10 minutes.
[0022] Wherein, the concentration of the DON nucleic acid aptamer in step 2) is 1-25 μM.
[0023] The preparation method of the AuNPs polymer FOLSPR sensor described in the present invention specifically comprises the following steps:
[0024] 1) Clean the bare optical fiber with ultrapure water and blow dry with nitrogen. Then immerse the bare optical fiber in piranha solution and treat it at 80℃ for 40min. Then rinse it with ultrapure water, clean it with ultrasound and blow dry it with nitrogen to hydroxylate the end face of the optical fiber.
[0025] 2) The optical fiber is immersed in an APTES solution (volume ratio: APTES: ethanol: water = 1:1:98) and then repeatedly rinsed with ethanol and ultrapure water, and dried with nitrogen to make the end face of the optical fiber have rich amino groups.
[0026] 3) Immerse the optical fiber sensor in the AuNPs solution and rinse with ultrapure water. Then immerse the optical fiber in the PETMP solution (ethanol as solvent), rinse with ethanol and ultrapure water in turn, and blow dry with nitrogen. Then immerse the optical fiber in the AuNPs solution again, rinse with ultrapure water, and blow dry with nitrogen, and the AuNPs polymer can be assembled on the end face of the optical fiber.
[0027] 4) The optical fiber assembled with AuNPs polymers was immersed in a DON nucleic acid aptamer solution, incubated overnight, repeatedly rinsed with aptamer buffer to remove non-covalently bound DON nucleic acid aptamers, and dried with nitrogen gas to complete the preparation of the FOLSPR biosensor based on AuNPs polymers.
[0028] The present invention also includes the application of the FOLSPR biosensor based on AuNPs polymers in the detection of DON toxin.
[0029] The present invention also includes a method for detecting DON toxin, comprising the following steps:
[0030] 1) Scan the FOLSPR biosensor spectra and record the peak position of the LSPR peak of the sensor;
[0031] 2) immersing the FOLSPR biosensor in DON toxin solutions of different concentrations, incubating, and again performing spectral scanning on the FOLSPR sensor to calculate the shift values of the LSPR peak positions twice;
[0032] 3) The concentration of the DON sample was calculated using the relationship between the LSPR peak shift value and the DON concentration.
[0033] Wherein, the concentration of DON toxin is 0.05-200 ng / mL.
[0034] The present invention also compares the response of the AuNPs FO LSPR sensor based on AuNPs monomers and the AuNPs polymer FO LSPR sensor to DON. By detecting DON standard solutions of different concentrations, the signal deviation degrees of the two are compared, and the sensitivity of the two is analyzed.
[0035] The present invention provides a FOLSPR aptamer biosensor based on AuNPs polymers, which uses a multimode bare optical fiber end face as a sensing platform, AuNPs polymers as sensing materials, DON nucleic acid aptamers as specific capture elements, and transmits reflection spectra through Y-shaped optical fibers. The working mechanism of the sensor is shown in Figure 1. The AuNPs were connected to the end face of the optical fiber in two steps to form AuNPs polymers, and then the thiol-modified DON aptamer was fixed to the AuNPs polymer through a gold-sulfur bond (Au-S) to complete the construction of the optical fiber sensor. The first step of AuNPs treatment time, PETMP treatment time, second step of AuNPs treatment time, APTES treatment time, DON aptamer concentration and detection time were optimized. The specific binding of DON and aptamer causes the LSPR peak of the optical fiber sensor to shift, and the degree of shift is related to the concentration of DON, thereby achieving the purpose of quantitative detection of DON.
[0036] Installation and connection of fiber optic sensing system Figure 2 As shown. High-throughput multimode bare optical fiber is used to construct the FO LSPR sensor, and Y-type optical fiber is used for signal transmission between the light source, sensor and spectrometer. A halogen tungsten lamp (HL-2000, OceanOptics, USA) is used to provide 400-1000nm light. A CCD spectrometer (i-trometer, BW Tek., Newark, DE, USA) is used to receive the reflected light of the FO LSPR sensor, which has the function of receiving light from 99% Spectralon TM Reflectance Standard (Labsphere Inc., North Sutton, USA) Interface for reflectance spectroscopy.
[0037] If the optical fiber sensor is damaged, it can be reused by cutting the damaged part and grinding and polishing the end face.
[0038] Beneficial effects: Compared with the prior art, the present invention has the following advantages: the detection method is fast and convenient; the detection work can be carried out on site; the detection personnel have low operating skills requirements; the sensors of the present invention can be used in batches to detect a large number of samples in a short time. The optical fiber LSPR sensor prepared by the present invention has high sensitivity for DON toxin detection, with a minimum detection limit of 0.05ng / mL, and has high specificity for detecting DON toxin in food, and the detection results are accurate and reliable. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 , schematic diagram of FO LSPR biosensor for detecting DON;
[0040] Figure 2 , the construction of AuNPs polymers and the “hotspot effect”;
[0041] Figure 3 ,FO LSPR sensing system;
[0042] Figure 4, characterization of AuNPs, (A) appearance of AuNPs solution; (B) TEM image of AuNPs; (C) UV-visible absorption spectrum of AuNPs; (D) particle size distribution of AuNPs;
[0043] Figure 5 , characterization of FOLSPR sensor, (A) optical fiber based on AuNPs monomer under scanning electron microscope; (B) AuNPs polymer on the end face of optical fiber under scanning electron microscope; (C) absorption peak of optical fiber based on AuNPs monomer; (D) absorption peak of optical fiber with AuNPs polymer;
[0044] Figure 6 , FO LSPR sensor condition optimization, (A) the effect of the first connection time on the formation of AuNPs polymers; (B) the effect of PETMP treatment time on the formation of AuNPs polymers (C) the effect of the second connection time on the formation of AuNPs polymers (D) the effect of 1% APTES treatment time on the formation of AuNPs polymers (E) LSPR shift response values of different concentrations of DON nucleic acid aptamers to 10ng / ml DON solution (F) The effect of incubation time on LSPR shift;
[0045] Figure 7 , Detection of DON toxin by optical fiber LSPR sensor; (A) LSPR spectra of DON solutions with different concentrations; (B) Nonlinear relationship between LSPR red shift and DON concentration; (C) Linear relationship between LSPR red shift and the logarithm of DON concentration;
[0046] Figure 8 , Selectivity analysis of fiber LSPR sensors;
[0047] Fig. 9 , the responses of FO LSPR sensors based on AuNPs polymers and AuNPs monomers to different concentrations of DON. DETAILED DESCRIPTION
[0048] The following examples can further illustrate the preparation of the composite material of the present invention and the preparation and electrochemical performance of its electrode material.
[0049] Example 1 Preparation and characterization of AuNPs
[0050] During the whole reaction process of synthesizing AuNPs, 100 ml of chloroauric acid (0.01% wt) was added to a 250 ml three-necked flask and heated to boiling. Then, 3 ml of 1% sodium citrate solution was quickly added dropwise to the reaction solution, and the solution was heated and refluxed. After the reaction continued for 15 min, the heating was stopped and the solution was cooled to room temperature (25°C). The prepared AuNPs solution was collected, sealed and stored at 4°C. Figure 4 As shown in A, the synthesized AuNPs have a wine red appearance. The UV-visible absorption spectrum of the AuNPs solution was measured using an optical fiber sensing system. The absorption peak is located at 524 nm ( Figure 4 C). Microscopic characterization using transmission electron microscopy ( Figure 4 B), and the particle size distribution was tested with a particle size distribution analyzer ( Figure 4 D), it can be found that the AuNPs synthesized in the present invention are mainly distributed around 21 nm.
[0051] Example 2 Preparation of FOLSPR Sensor
[0052] The bare optical fiber with a flat end face was cleaned with ultrapure water and dried with nitrogen. Then the bare optical fiber end face was immersed in piranha solution (98% sulfuric acid and 30% hydrogen peroxide in a volume ratio of 7:3) for 2-3 cm, treated at 80°C for 40 minutes, then rinsed with ultrapure water, and then immersed in ultrapure water, ultrasonically cleaned for 5 minutes, taken out and dried with nitrogen to obtain a hydroxylated optical fiber sensor.
[0053] Subsequent optical fiber processing and detection were carried out at 25°C. The hydroxylated optical fiber end face was immersed in a 1.0% 3-aminopropyltriethoxysilane (APTES) solution (volume ratio: APTES: ethanol: water = 1:1:98) for about 1-2 cm and treated for 12 hours. APTES was connected to the optical fiber end face through hydrolysis and condensation, forming abundant amino groups on the optical fiber end face. Then, it was repeatedly rinsed with ethanol and ultrapure water in turn, and dried with nitrogen to obtain an amino-containing optical fiber sensor.
[0054] The amino-modified optical fiber sensor was immersed in the AuNPs solution for about 0.5 cm and treated for 5 hours. The AuNPs were modified to the end face of the optical fiber through gold-amine bonds. It was rinsed with ultrapure water to remove non-covalently bound AuNPs and dried with nitrogen to obtain an optical fiber with sparsely distributed AuNPs monomers.
[0055] Then, the optical fiber was immersed in 4 mg / mL pentaerythritol tetra(3-mercaptopropionate), PETMP (ethanol as solvent) for 3 hours, rinsed with ethanol and ultrapure water in turn, and dried with nitrogen. PETMP contains four thiol groups, and some thiol groups are firmly anchored to AuNPs through Au-S bonds, which makes the surface of AuNPs have a rich layer of thiol groups, which can combine with additional AuNPs. The optical fiber was immersed in the AuNPs solution again for 5 minutes, rinsed with ultrapure water and dried with nitrogen. The AuNPs on the end face of the optical fiber and the AuNPs in the solution form the structure of AuNP-(PETMP-AuNPs)n through the Au-S bond, which can assemble on the end face of the optical fiber to form an AuNPs polymer ( Figure 2 ).
[0056] The optical fiber assembled with AuNPs polymer was immersed in a 15.0μM thiol-modified DON aptamer solution for 12 hours and repeatedly rinsed with aptamer buffer to remove non-covalently bound DON aptamers. DON aptamers are connected to the surface of AuNPs through thiol groups, eventually forming a structure of optical fiber-AuNPs polymer-DON aptamer, completing the preparation of AuNPs polymer DON FO LSPR biosensor. Keeping the optical fiber end face clean and not worn during the preparation of the sensor is the key to success.
[0057] Example 3 Characterization of sensors based on AuNPs polymers and AuNPs monomers and comparison of signal strength
[0058] The signal of the fiber LSPR-based biosensor is closely related to the distribution of AuNPs on the fiber end face. Using scanning electron microscopy, the fiber directly connected to AuNPs and the fiber connected to AuNPs polymers were characterized. Figure 5 A and Figure 5 As shown in B. After the AuNPs are connected to the optical fiber, the AuNPs are randomly distributed on the end face of the optical fiber. This method can enhance the signal intensity of the LSPR by directly increasing the density of AuNPs monomers on the end face of the optical fiber. The disadvantage is that when the treatment time is long, the AuNPs are prone to aggregation (such as Figure 5 A). AuNPs polymers were constructed on the end face of the optical fiber by a two-step AuNPs connection method. The AuNPs polymers were formed by coupling multiple AuNPs via PETMP. The polymers were randomly distributed on the end face of the optical fiber with a high density. The AuNPs in a single polymer were clearly spaced and not aggregated. The UV-visible spectra of the AuNPs monomers and AuNPs polymers on the end face of the optical fiber were measured by the optical fiber sensing system (e.g. Figure 5 C and Figure 5D). Randomly assembled AuNPs monomers also have nanogap structures, but the generation of hot spot effect depends on the gap distance between two nanoparticles. The experimental results show that compared with the direct connection method, the two-step assembly method has a shorter processing time and is easier to construct an effective nanogap structure in actual operation, which increases the intensity of LSPR signal by about 4.0 times.
[0059] Example 4 Optimization of sensor preparation conditions
[0060] First, we optimized the time for connecting AuNPs in the first step and used AuNPs to treat the optical fiber for 1h, 2h, 3h, 4h, 5h, 6h, 7h, and 8h. Figure 6 The result shown in A is the change of absorbance of the polymer on the surface of the optical fiber at 520nm with the treatment time. The results show that when the second step AuNPs treatment time is 5min, the LSPR signal of the optical fiber with the first step AuNPs treatment time of 5h reaches saturation. After 5h, the randomly distributed AuNPs monomers on the end face of the optical fiber continue to increase. Although aggregation will not occur in the first step of connection, the density of the AuNPs polymers formed on the end face of the optical fiber is high during the second step of connection, and aggregation is prone to occur. In the next three hours, the absorbance continued to increase because the AuNPs polymers on the end face of the optical fiber aggregated, causing an increase in the absorption peak near 600nm. Therefore, 5h was selected as the connection time for the first step.
[0061] Secondly, we optimized the treatment time of 4 mg / mL PETMP for 1 h, 2 h, 3 h, 4 h, and 5 h ( Figure 6 B). PETMP with appropriate concentration can form a stable polymer structure during the second step of connection. If the concentration is too low, the formed polymer structure is less stable and easily destroyed. If the concentration is too high, the number of thiol groups on the surface of AuNPs connected to the end face of the optical fiber in the first step will increase, and AuNPs will be easily aggregated in the second step of connection. Finally, it is concluded that a stable optical fiber sensor with a strong LSPR signal can be obtained when the treatment time is 3h.
[0062] Then we optimized the second AuNPs treatment time (1min, 2min, 3min, 4min, 5min, 6min, 7min, 8min, 9min, 10min) ( Figure 6 C). At 1-5 min, the AuNPs polymer increases with the increase of treatment time, and then increases again in the following 5 min. The AuNPs polymer aggregates due to excessive binding of AuNPs, and the hot spot effect disappears. The absorbance of the polymer at 520 nm decreases, and then increases slightly at 520 nm due to the large aggregation of AuNPs at the end face of the optical fiber.
[0063] The optical fiber was treated with 1% APTES for different time periods (2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, and 18h). The AuNPs polymers on the end surface of the optical fiber increased with the increase of APTES treatment time and reached the maximum at 12 hours. Subsequently, increasing the treatment time had no significant effect on the absorbance at 520nm, and the value tended to be stable. Therefore, the optimization result of 1% APTES treatment time was 12h ( Figure 6 D).
[0064] The coverage of DON aptamers (5'-(SH)-(CH2)6-GCA TCA CTA CAG TCA TTACGC ATC GTA GGG GGG ATC GTT AAG GAA GTG CCC GGA GGC GGT ATC GTG TGA AGT GCTGTC CC-3', prepared by Shanghai Bioengineering Co., Ltd.) on the surface of AuNPs polymers is crucial to the detection limit, sensitivity and response time of the sensor. In order to achieve an optimal sensing performance, the density of DON aptamers needs to reach a high level. However, when the concentration of DON aptamers is too high, the density of DON aptamers on the surface of AuNPs polymers is extremely high, resulting in a steric effect, making it difficult for DON to bind to DON aptamers. Figure 6 The results show that when the concentration of DON aptamer treated with AuNPs polymer is 15 μm / L, the LSPR shift of the sensor to 10 ng / mL DON solution reaches the maximum value ( Figure 6 E).
[0065] Example 5 Optimization of sensor response time
[0066] The incubation time required for the sensor was optimized using treatment times of 1h, 4h, 8h, 12h, 16h, 20h, and 24h. Within 0-12 hours, the optical fiber continuously captured DON molecules through the DON aptamer, and the LSPR offset value continued to increase. After 12 hours, the DON nucleic acid aptamer of the sensor reached saturation and could no longer capture DON in the solution. Therefore, the incubation time of the sensor was set to 12h ( Figure 6 F).
[0067] Example 6 Detection of DON toxin by FOLSPR sensor
[0068] The optimized LSPR sensing system was used to detect DON standard solutions of different concentrations (0.05ng / mL, 0.1ng / mL, 0.5ng / mL, 1ng / mL, 5ng / mL, 10ng / mL, 50ng / mL, 100ng / mL, 200ng / mL). When the DON aptamer captures DON, the refractive index in the local environment of the AuNPs polymer increases, so the LSPR peak is red-shifted. In addition, the hot spot effect of the polymer enhances the red-shift, and the red-shift value is positively correlated with the DON concentration. Figure 7 A is the normalized LSPR spectrum with the increase of DON concentration. The relationship between the red shift degree and DON concentration is shown in Figure 7 As shown in B, the red shift increases with the increase of DON concentration and tends to be stable when reaching higher concentrations. The relationship between LSPR shift and concentration is logarithmic, but it is linearly related to the logarithm of DON concentration ( Figure 7 C). The logarithmic value of the concentration was linear in the range of 0.05 to 200.0 ng / mL (R 2 =0.9934, LOD=0.04ng / mL, LOQ=0.05n / mL).
[0069] Example 7 Selectivity Analysis of Sensors
[0070] When food is moldy, it often produces a variety of toxins. In order to investigate the selectivity of the constructed LSPR biosensor, the fiber optic LSPR sensor was used to detect 10 ng / mL DON, AFB1, FB1, OTA and T-2 solutions under the same conditions, and the LSPR shift of different toxins was analyzed. Figure 8 ). The results showed that only DON had a significant red shift of 11.0nm. Among them, AFB1, FB1, and T-2 produced red shifts of 0.9, 1.1, and 1.3nm, while OTA produced a blue shift of 1.7nm, which is reasonable because the concentration of the analyte used for specific detection is relatively high. This shows that the capture and signal generation of DON by the sensor is not affected by interfering molecules, which depends on the specific binding of DON and DON aptamer.
[0071] Example 8 Performance comparison of sensors based on AuNPs polymers and AuNPs monomers
[0072] The optimized FOLSPR sensors based on AuNPs monomers and AuNPs polymers were used to detect DON standard solutions of different concentrations (0.05, 1, 10, 100 ng / mL). Through the combination of DON and the aptamer, both FOLSPR sensors will produce a red-shift response, but the FOLSPR sensor based on AuNPs shows a higher and more sensitive red-shift response. In the 0.05 ng / mL DON standard solution, the optical fiber based on AuNPs monomers produced a negative shift, which is similar to the test results of the 0 ng / mL DON solution, but the optical fiber based on AuNPs polymers can still produce a positive LSPR shift. The test results of the two sensors on 1, 10, and 100 ng / mL DON solutions show that the LSPR signal shift value of the FOLSPR sensor based on the AuNPs polymer structure is about 3.4 times higher than that based on the AuNPs monomer structure. The LOD test result of the FOLSPR sensor based on AuNPs monomer structure was 0.32ng / ml, while the LOD of the FOLSPR sensor based on AuNPs polymer was 0.04ng / mL, with the sensitivity increased by about 7.8 times.
[0073] Example 9: Detection of corn samples by sensors
[0074] Dry corn was used as a sample for reagent detection and spike recovery test. Three spike concentrations of 0.2 mg / kg, 0.4 mg / kg and 1 mg / kg were set for analysis, and three replicates were set for each concentration and blank. The feasibility of the method was verified by ELISA. The test results are shown in Table 1. The method has good accuracy for the quantitative detection of DON (the recovery rate is between 105.2% and 113.6%). In addition, compared with the experimental results of the existing ELISA detection method, P>0.05, indicating that there is no significant difference between the two detection methods, and they can be used for DON detection in actual samples.
[0075] Table 1
[0076] Sequence Listing Information: DTD version: V1_3 File name: AuNPs.xml Software Name: WIPO Sequence Software version: 2.1.0 Date of creation: 2024-11-22 Basic Information: Current Applications / IP Offices: CN Current application / Application number: 2022107455483 Current application / Application date: 2022-06-28 Current application / applicant profile name: Jiangsu university of science and technology Applicant's name: Jiangsu University of Science and Technology Applicant's Name / Language: zh Applicant's name or title / Latin name: Jiangsu university of science and technology Invention Title: FOLSPR aptamer sensor based on AuNPs polymer and its preparation method and application (zh) Total number of sequences: 1 sequence: Serial Number(ID): 1 Length: 80 Molecule Type: DNA Feature Position / Qualifier: - source, 1..80 > mol_type, other DNA > organism, synthetic construct Residue: gcatcactac agtcattacg catcgtaggg gggatcgtta aggaagtgcc cggaggcggt 60 atcgtgtgaa gtgctgtccc 80 END
Claims
1. A method for preparing a FOLSPR biosensor based on AuNPs polymers, wherein the FOLSPR biosensor is obtained by fixing a thiol-modified DON nucleic acid aptamer on an AuNPs polymer via a gold-sulfur bond, wherein: The following steps are involved: 1) Assembling AuNPs polymer optical fibers: 2) Immobilize the thiol-modified DON nucleic acid aptamer on the optical fiber assembled with AuNPs polymer; The step 1) of assembling the optical fiber of AuNPs polymer comprises the following steps: 1.1) Preparation of AuNPs; 1.2) Clean and hydroxylate the end face of the optical fiber; 1.3) The modified optical fiber of step 1.2) is immersed in the APTES solution; 1.4) The modified optical fiber in step 1.3) is modified with AuNPs via gold-ammonia bonds; 1.5) The modified optical fiber of step 1.4) is treated with PETMP to modify the AuNPs on the optical fiber with thiol groups; 1.6) The optical fiber treated in step 1.5) is further assembled through Au-S bonds to obtain an optical fiber of AuNPs polymers.
2. The method for preparing the FOLSPR biosensor based on AuNPs polymer according to claim 1, characterized in that: The sequence of the DON nucleic acid aptamer is 5'-(SH)-(CH2)6-GCA TCA CTA CAG TCA TTA CGC ATCGTA GGG GGG ATC GTT AAG GAA GTG CCC GGA GGC GGT ATC GTG TGA AGT GCT GTC CC-3'.
3. The method for preparing the FOLSPR biosensor based on AuNPs polymer according to claim 1, characterized in that: The particle size of the AuNPs polymer is 16-28 nm.
4. The method for preparing the FOLSPR biosensor based on AuNPs polymer according to claim 1, characterized in that: In step 1.3), the concentration of APTES solution is 1.0%, the APTES treatment time is 2-18 h, the AuNPs treatment time for optical fiber in step 1.4) is 1-8 h, the PETMP treatment time in step 1.5) is 1-5 h, and the treatment time in step 1.6) is 1-10 min.
5. The method for preparing the FOLSPR biosensor based on AuNPs polymer according to claim 1, characterized in that: The concentration of DON aptamer in step 2) is 1-25 μM.
Citation Information
Patent Citations
Deoxynivalenol nucleic acid aptamer and application thereof
CN102559686A